Factor VIII-Related Antigen in Cerebrospinal Fluid - Garcia, V Vicente; Alberca, I; Borrasca, A Lopez (Thrombosis and Haemostasis, 1983)
A hundred and one samples of cerebrospinal fluid (CSF) were obtained from patients with bacterial meningitis (18), viral meningitis (9), lymphoproliferative disorders (33), 15 with meningeal infiltrations, multiple sclerosis (8), stroke (8) and 25 subjects with normal CSF. All samples were studied for VIIIR: Ag with specific and sensitive immunoradiometric assay (IRMA) and Laurell’s technique.Prothrombin and factor IX antigenic activities were investigated by Laurell’s technique. Simultaneously, plasma specimens from ten patients with bacterial meningitis were evaluated. Only a selective increase of VIIIR: Ag was demonstrated in CSF from bacterial meningitis whereas prothrombin and factor IX were not detected. VIIIR: Ag plasma and CSF levels were uncorrelated. Similarly, no relationship could be established between the degree of elevation of VIIIR: Ag in the CSF and their protein concentration.These findings suggest that VIIIR :Ag elevation in CSF has diagnostic value for bacterial meningitis and that disruption of the blood-brain barrier is not responsible for their elevated levels. Accordingly, the presence of VIIIR :Ag in CSF may be an indication of endothelial damage in the choroid plexi.
Keywords: Cerebrospinal fluid; Factor VIII-related antigen; Bacterial meningitis